Spiderwebs and silk : tracing evolution from molecules to genes to phenotypes - Craig, Catherine Lee (Oxford University Press, 2003)
This book links the molecular evolution of silk proteins to the evolution and behavioral ecology of web-spinning spiders and other arthropods. Craig's book draws together studies from biochemistry through molecular genetics, cellular physiology, ecology, and behavior to present an integrated understanding of an interesting biological system at the molecular and organizational levels.